Single-Needle Lateral Sacroplasty Technique - Nicholson, P.J.; Hilditch, C.A.; Brinjikji, W.; Tsang, A.C.O.; Smith, R. (American Journal of Neuroradiology, 2019)
SUMMARY: Sacral insufficiency fractures result in significant morbidity, and percutaneous sacroplasty has emerged as a promising technique for their treatment. We present a technical note regarding our method of treating these fractures using a “single-needle” lateral technique with a combination of conebeam CT and biplane fluoroscopy. We treated 10 patients, in whom the median Visual Analog Scale pain score decreased from 7.0 to 0 (P < .001). We concluded that single-needle sacroplasty is feasible and safe using this technique.